Obesity and the Risk for a Hematological Malignancy: Leukemia, Lymphoma, or Myeloma - Lichtman, Marshall A. (AlphaMed Press, 2010)
The aggregate of epidemiological studies indicates a significantly elevated risk for cancer in people with a high body mass index (BMI); a “dose–response” effect exists with increasing risk as BMI increases from the normal to overweight to obese categories. Successful sustained weight loss decreases future risk. The relationship of being overweight to the risk for leukemia in the aggregate has been supported in several large cohort studies and two meta-analyses of cohort and case–control studies. One meta-analysis found an elevated risk for each of the four major subtypes of leukemia. A significant association between the risk for non-Hodgkin's lymphoma and elevated BMI was supported by a meta-analysis of 13 cohort and nine case–control studies. The risk for diffuse large B-cell lymphoma may be especially significant. A high BMI increases the risk for myeloma, as judged by a meta-analysis of 11 cohort and four case–control studies. The biological relationship of obesity to the risk for cancer (biological plausibility) is unresolved. The two major causal final pathways could be “inductive” or “selective.” The metabolic, endocrinologic, immunologic, and inflammatory-like changes resulting from obesity may increase the cell mutation rate, dysregulate gene function, disturb DNA repair, or induce epigenetic changes, favoring the induction of neoplastic transformation (inductive). Alternatively, obesity may create an environment in which pre-existing clones that are dormant are permitted (selected) to emerge.